Carapa wohllebenii (Meliaceae), a new tree species from montane forests in the Democratic Republic of Congo, Rwanda, and Burundi - Fischer, Eberhard; Killmann, Dorothee; Leh, Burkhard; Janssens, Steven B. (Phytotaxa, 2021)
Carapa wohllebenii is described as a new tree species from the Democratic Republic of Congo, Rwanda, and Burundi. Its affinities to Carapa grandiflora are discussed. It differs in a number of morphological features; the most prominent being the oblanceolate-oblong leaflets with distinctly mucronate apex and a length/width ratio of 3.2–4.7 (vs. oblong ovate leaflets with mucronulate apex and a length/width ratio of 1.9–2.7 in C. grandiflora). A molecular phylogeny of Carapa is presented that clearly indicates the distinct phylogenetic position of both species. Based on the current knowledge, the new species is given a preliminary conservation assessment of LEAST CONCERN (LC). Carapa grandiflora is here for the first time recorded from the Democratic Republic of Congo.